Design And Performance Evaluation of An Esp32-Based Automatic Irrigation Sluice Gate Prototype Using an Ultrasonic Water Level - Muhammad Aidil Priono; Eko Gunawan; Indie Arsyta; Suparman Suparman (Akademi Komunitas Perkebunan Yogyakarta, 2026)
Water gate operation in irrigation systems is generally performed manually, which may delay responses to changes in water level. Such conditions can result in inefficient water discharge regulation and increase the risk of water overflow. This study aims to design and develop a prototype of an automatic irrigation sluice gate system using an ultrasonic sensor based on an ESP32 microcontroller. The research consisted of system design, hardware assembly, microcontroller programming, and prototype performance testing. The ultrasonic sensor was employed to measure water level changes, while the ESP32 processed the acquired data to control a servo motor as the gate actuator. Experimental results demonstrated that the proposed system responded rapidly and stably to variations in water level with satisfactory measurement accuracy throughout the testing range. The implemented control mechanism successfully operated the sluice gate automatically according to water level conditions. Therefore, the proposed system has the potential to improve irrigation management efficiency while reducing human error associated with manual gate operation.